Textile Dimension of the Department of Fabric and Clothing Design of KSADA - Vasylieva, Maryna; Malik, Tetyana (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article explores the history and development of the Department of Fabric and Clothing Design at KSADA, outlining its educational focus and the evolution of training programs. Attention is given to the disciplines taught in the past and present, as well as to the results of student learning demonstrated in course and diploma projects. The authors stress the importance of updating knowledge related to the functions and connections of textile design not only with costume design but also with interior, environmental, and exhibition practices. This approach has led to the creation of innovative textile design products that expand beyond “classical” forms and renew the aesthetic dimension of design. The article notes that in 2000 the Department of Artistic Modeling of Textiles (AMT) was reorganized into the Department of Artistic Modeling of Fabrics and Clothing (AMFC), with specializations in both textiles and clothing. Today, the department functions as the Department of Fabric and Clothing Design (FCD), where students are trained in textile design within the broader framework of costume design, sustainable fashion, and ecological design. The purpose of the article is to trace the history and prospects for the development of textile design at the FCD Department. The study demonstrates that the central role of textile design within the educational program “Clothing (Shoe) Design” is the development of original techniques for decorating and finishing garments. These practices allow students to translate artistic, figurative and emotional-psychological aspects of design into material form while istablishing associative links with cultural sources. To achieve this, students study classical and Ukrainian folk decorative traditions alongside exclusive techniques such as hand weaving, embroidery, and painting. This contributes to a more sustainable and environmentally conscious approach to fashion. Textile design is thus presented as one of the oldest yet continually relevant means of decorating and individualizing clothing, and as a key trend in contemporary fashion design practices.